Жүкті тасымалдау шартының ұғымы жəне құқықтық табиғаты - Əкімжанова, М.Т. (ҚарМУ басп, 2011)
В статье исследованы теоретические проблемы понятия и правовой природы договора перевозки грузов в науке гражданского права, который является основным в системе транспортных договоров. В рамках темы исследования автор изучил научные взгляды ученых-цивилистов, проанализировал точки зрения о правовой природе договора перевозки грузов. В статье также дана научно-правовая оценка особенностям гражданско-правового регулирования договора перевозки грузов, разработаны предложения по совершенствованию гражданского и транспортного законодательства. The theoretical problems of concept and legal nature of the contract of transportation of cargoes in science of civil law which is the basic contract in system of transport contracts are investigated in article. Within the limits of theme of research the author has studied scientific views of scientists of civil law, has analysed the points of view about the legal nature of the contract of transportation of cargoes. The scientifically-legal estimation is given to features of civil-law regulation of the contract of transportation of cargoes, offers about perfection of the civil and transport legislation are developed.